Predictors of Intent to Receive the COVID-19 Vaccination Among the Population in the Kingdom of Saudi Arabia: A Survey Study - Alobaidi,Sami (Journal of Multidisciplinary Healthcare, 2021)
Sami Alobaidi Department of Internal Medicine, University of Jeddah, Jeddah, Saudi ArabiaCorrespondence: Sami AlobaidiDepartment of Internal Medicine, University of Jeddah, Jeddah, Saudi ArabiaTel +966566482649Email salobaidi@uj.edu.saBackground: The COVID-19 pandemic had a significant economic and social impact on the Kingdom of Saudi Arabia. This study explored various factors influencing the COVID-19 vaccination intention and the applicability of the health belief model (HBM) to explore vaccination intention among the population of Saudi Arabia.Methods: This is an online survey conducted between January 6, 2021, and January 19, 2021, using a GoogleTM form questionnaire among Saudi population. The questionnaire aimed to assess the factors that influence the intent to receive the vaccine, by evaluating demographic details, COVID-19 experience and health self-assessment, acceptability of COVID-19 vaccination and preferences and health belief regarding COVID-19 illness and vaccination.Results: The survey generated a total of 1333 responses from all over the 13 provinces of the Kingdom. The participants had mixed perceptions regarding the susceptibility and severity of COVID-19. A total of 959 (71.9%) subjects responded positively to COVID-19 vaccine intent. Those with > 15,000 SR per month income, no past exposure to COVID-19, and comorbidities reported significantly higher intention to take vaccination (p< 0.05). Among the HBM variables, the perceived susceptibility construct (OR=3.82, 95% CI 1.64– 8.94) and perceived benefit construct (OR=7.59, CI 1.65– 34.86) were important facilitators for a definite intention to vaccinate. The perceived barriers construct (safety [OR= 0.062, CI 0.03– 0.15]; side effects of the vaccine [OR=0.31, CI 0.13– 0.75]) and cues to action construct (OR=0.32, CI 0.13– 0.77) were the significant factors hindering the uptake of COVID-19 vaccine. However, the perceived severity construct did not play an important role in predicting definite intention to receive the COVID-19 vaccine ...